KINERJA UNIT USAHA SIMPAN PINJAM KOPERASI PEGAWAI NEGERI DHARMA WIGUNA KOTA DENPASAR - Suyasa, I Gusti Ngurah Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; Volume 02. No.02. Tahun 2013, 2013)
Abstract: Performance Of Savings and Loan Business Unit Of Dharma Wiguna Civil Servants Cooperative Denpasar City . Technical analysis applied was the Balanced Scorecard. The results showed that the predicate of cooperative seen from financial aspects is healthy. The members aspects (customers), the results was obtained, showing that the quality of the customer service of Savings and Loan Business Unit of Dharma Wiguna Civil Servants Cooperative of Denpasar City is satisfactory. Aspects of internal processes this showed the quality of the customer service satisfaction is positive or good. Aspects of growth and learning is employee satisfaction of Business Unit Savings and Loans of Dharma Wiguna Civil Servant Cooperative of Denpasar City is positive or good. Based on Composite Index Calculation (CI) overall showed that the performance of the cooperative was very good performance.   Abstrak: Kinerja Unit Usaha Simpan Pinjam Koperasi Pegawai Negeri Dharma Wiguna Kota Denpasar . Tehnik analisis yang digunakan adalah Balanced Scorecard. Hasil penelitian menunjukkan predikat koperasi dari aspek keuangan cukup sehat. Aspek anggota (pelanggan) menunjukkan kepuasan anggota  terhadap kualitas layanan Unit Usaha Simpan Pinjam Koperasi Pegawai Negeri memuaskan. Aspek proses internal menunjukkan kepuasan anggota  terhadap kualitas layanan positif atau baik. Aspek pertumbuhan dan pembelajaran menunjukkan kepuasan karyawan terhadap Unit Usaha Simpan Pinjam Koperasi Pegawai Negeri Dharma Wiguna Kota Denpasar adalah positif atau baik. Berdasarkan Perhitungan Indeks Komposit (IK) secara keseluruhan menunjukkan kinerja sangat baik.
Keywords: saving, loan, business, cooperative, denpasar